THE USE OF PHET TECHNOLOGY IN TEACHING PHYSICS - Ochilova Ozoda Odilovna; Absalyamova Ilmira Ildarovna; Abdullayeva Shoira Isajanovna; Xalilova Nozliya Samadovna (PEDAGOGS, 2024)
Annotation: This article explores the integration of PHET (Physics Education Technology) simulations in teaching physics, highlighting their role in enhancing students' understanding of complex concepts. PHET simulations offer interactive, visual, and dynamic learning tools that are beneficial for both students and teachers. This study examines existing literature, analyzes the effectiveness of PHET in physics education, and suggests methods for successful integration. The findings reveal that PHET contributes to better conceptual understanding and engagement, especially when used in conjunction with traditional teaching methods.